What’s the role of humanities in academic reading and writing processes? Martha Nussbaum and François Rastier - Torres Perdigón, Andrea (Íkala, Revista de Lenguaje y Cultura, 2016)
This article exposes a reflection about humanities’ role as a useful tool to help students with the reading and writing difficulties that they experience nowadays in a global context. Based on the fact that these difficulties exist in the Hispanic context, the article supports that there might be a change in the way we understand knowledge in universities. This transformation is explored from two angles: an essay by Martha Nussbaum, published in 2010, and another one by François Rastier, published in 2013. A comparative analysis of both texts allows us to establish some similarities regarding the role that these sciences of meaning may have within universities, facing the consequences that the transformation of this conception of knowledge may be generating in higher education.